Ảnh hưởng của oligome dầu lanh epoxy hóa (OELO) đến tính chất cơ học của polyme epoxy. Phần 2. Độ bền dai tách lớp và tính chất cơ học của vật liệu polyme compozit trên cơ sở nhựa epoxy epikote 828/OELO gia cường vải thủy tinh, đóng rắn bằng xyanetyldiety - Trung, Đặng Hữu; Ninh, Trần Hải; Diệu, Trần Vĩnh; Bích Thủy, Nguyễn Thị; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2014)
Epoxy resins are thermosetting polymers for many applications with required high modulus and strength, low creep, and good ferformance at elevated temperatures. However, their brittleness, low toughness, and poor impact resistance result in their limitation of applications. In this work, oligomers of epoxidized linseed oil (OELO) were dispersed in the epoxy resin epikote 828 matrix. The obtained testing results showed that the Izod impact strength of glass fabric/epoxy composites significantly increased by 37.2 % from 179.05 KJ/m2 to 245.65 KJ/m2 just by adding 6 phr (part per hundred of resin) OELO. While the mode-I interlaminar fracture toughness for crack initiation and propagation also improved by 13.2 % and 12.5 % respecttively, by content of 6 phr OELO in compositions. The fracture surfaces of specimens were observed by scanning electron microscopy, and the interlaminar fracture toughness was analysed. Keywords: Interlaminar fracture toughness, Epoxy resin, Cyanethyldiethylenetriamine, Epikote 828, Epoxidized linseed oil, glass fiber